Synthesis, Structural and Optical Characterization of Titanium Dioxide Doped by (Ce, Yb) Dedicated to Photonic Conversion - Zobair El Afia; Mohamed Youssef Messous; Mohamed Cherkaoui; Mounia Tahri (Indonesian Journal of Chemistry, 2020)
The synthesis of TiO2 co-doped by (Ce, Yb) rare earth couple has been realized. This couple of rare earth can convert a high-energy photon to two low energy photons to enhance the energy efficiency of silicon solar cells. The undoped, 2% Ce doped- and (2% Ce, 4% Yb) Codoped- Titanium oxide were prepared by the co-precipitation method. The Infrared spectroscopy FTIR-ATR analysis indicates a continuous visible absorption in the 750–400 cm–1 region, confirming the formation of a titanium-oxygen bond. The X-Ray Diffraction characterization showed the dominance of the rutile crystalline phase with the presence of anatase one and the calculated crystallite size is between 7 to 13 nm. The X-Ray Fluorescence confirms the insertion of the dopants while the Inductively Coupled Plasma Mass Spectrometry ICP-MS showed the ratio 2 between Ce and Yb concentration. The thermogravimetric analysis indicated that Ce/Yb doped titanium was thermally stable. The absorption in the UV-visible (200 and 1000 nm) has been improved proportionally with the dopants.